Adjuvant composite cold atmospheric plasma therapy increases antitumoral effect of doxorubicin hydrochloride - Kniazeva, Volha; Tzerkovsky, Dzmitry; Baysal, Ömür; Kornev, Alexander; Roslyakov, Evgeny; Kostevitch, Serhei (Frontiers in Oncology, 2023)
Cancer is a major public health problem worldwide. The International Agency for Research on Cancer estimates that globally, 1 in 5 people develop cancer during their lifetime, and 1 in 8 men and 1 in 11 women die from the disease. The uprise of targeted antitumor drugs significantly in-crease the effectiveness of treatment of several tumor diseases however the process of developing new antitumor drugs becoming more difficult due its expensiveness and resistance of tumors to therapy. Overall, the area of antitumor therapy is still far from a cardinal breakthrough. In this regard, along with the improvement of combined chemotherapy, which is a standard practice in oncology, and the search for new ways in the treatment of tumors), approaches aimed at improving the effectiveness of common antitumor agents are promising. The antineoplastic effect of cold atmospheric plasma has already been demonstrated successfully in vivo and in vitro; however, the effect of composite cold atmospheric plasma with a specific group of ions on lymphosarcoma and its use in complex therapy has not yet been studied. The in vivo study on Pliss lymphosarcoma rats model revealed inhibition of the growth of transplanted tumors in the groups exposed to composite cold plasma with a duration of 3, 7, and 14 days compared to the intact control group. It was also found that a combination of chemotherapy with ionic therapy reduced tumor volume in three times and showed a positive effect, especially in combination with doxorubicin hydrochloride 5 mg/kg and 14 days of PERENIO IONIC SHIELD ™ ionic therapy. The composite cold plasma therapy with controlled ionic formula emitted by PERENIO IONIC SHIELD ™ in complex therapy of lymphosarcoma in rats presented a promising antitumor effect, especially in combination with chemotherapy.